Designing a Model for Institutionalizing Organizational Spirituality with an Emphasis on Ethical Climate: A Case Study in the Khorasan Razavi Education Department - Niknam Fadafan, Fatemeh; Naseri, Nazia Sadat; Hashemiannejad, Farideh (Digital Transformation and Administration Innovation, 2024)
In the complex and dynamic world of today’s organizations, institutionalizing spirituality in the workplace is considered a key factor in improving organizational performance, enhancing employee commitment, and promoting an ethical climate. This is especially important in educational organizations, which serve as the foundation for the development of societal values. In such settings, fostering and reinforcing organizational spirituality in interaction with the ethical climate can create the groundwork for improving both individual and organizational functions. The present study aimed to design a model for institutionalizing organizational spirituality with an emphasis on the dimensions of ethical climate in the Khorasan Razavi Department of Education, in order to identify and analyze the reciprocal effects of the components of these two variables. The study is applied in nature and employs a mixed-methods approach (qualitative–quantitative). In the qualitative phase, using the grounded theory method and conducting semi-structured interviews with 15 educational and administrative experts, the key components of spirituality and ethical climate were extracted. In the quantitative phase, the conceptual model derived from the qualitative analysis was tested using structural equation modeling (SEM) and confirmatory factor analysis (CFA). The statistical population consisted of employees and managers of the Khorasan Razavi Department of Education. In the quantitative phase, stratified random sampling was employed, resulting in the collection and analysis of 320 completed questionnaires. The results of structural equation modeling showed that the dimensions of organizational spirituality—namely, meaning and purpose in work (β = 0.78), sense of belonging (β = 0.71), spiritual connection (β = 0.74), and ethical values (β = 0.69)—had a significant and positive impact on the organizational ethical climate (p < 0.001). Furthermore, the dimensions of ethical climate—namely, justice (β = 0.81), accountability (β = 0.76), empathy (β = 0.73), and organizational transparency (β = 0.79)—played an effective mediating role in the relationship between organizational spirituality and improvement in organizational performance. The model’s coefficient of determination (R²) indicated that 64% of the variance in the organizational ethical climate could be explained by the components of organizational spirituality. Based on the findings, strengthening spirituality in educational environments leads to improved employees’ mental health, increased productivity, enhanced accountability, and reduced organizational conflict. Education administrators can benefit from this model in macro-level policymaking, designing human resource development programs, and fostering an organizational culture grounded in spirituality and ethics. This research takes a step toward a deeper understanding of the interaction between spirituality and organizational ethics in educational settings and can serve as a foundation for future research in this area.